2007
DOI: 10.1007/s00449-007-0146-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing yield of S-adenosylmethionine in Pichia pastoris by controlling NH4 + concentration

Abstract: Yield of S-adenosylmethionine was improved significantly in recombinant Pichia pastoris by controlling NH(4)(+) concentration. The highest production rate was 0.248 g/L h when NH(4)(+) concentration was 450 mmol/L and no repression of cell growth was observed. Within very short induction time (47 h), 11.63 g/L SAM was obtained in a 3.7 L bioreactor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…[18] DCC was chosen for encapsulation and coating because of previous studies citing cartilage matrix as a potentially chondroinductive material. [13,15,16,31,32] The use of decellularized cartilage instead of native or devitalized cartilage is advantageous from clinical and commercial standpoints because of decreased immunogenicity and long-term storage of the material. Successful decellularization of tissues, i.e., complete removal of residual DNA and immunogenic antigens, may also eventually lead to safer xenogeneic tissue implants for all tissue types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] DCC was chosen for encapsulation and coating because of previous studies citing cartilage matrix as a potentially chondroinductive material. [13,15,16,31,32] The use of decellularized cartilage instead of native or devitalized cartilage is advantageous from clinical and commercial standpoints because of decreased immunogenicity and long-term storage of the material. Successful decellularization of tissues, i.e., complete removal of residual DNA and immunogenic antigens, may also eventually lead to safer xenogeneic tissue implants for all tissue types.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Previous studies have reported adipose derived stem cell (ASC) and bone marrow-derived mesenchymal stem cell (BMSC) differentiation in the presence of DCC. [3,12,13] One challenge with DCC-based scaffolds is that the mechanical function of the scaffolds may be compromised during the decellularization process. [4,11,14] To help fabricate a material with a compressive strength suitable for articular cartilage repair, combining DCC with a polymeric scaffold has previously been shown to achieve greater mechanical performance than DCC scaffolds alone.…”
Section: Introductionmentioning
confidence: 99%
“…Hematoxylin and eosin staining (H&E), immunohistochemistry (IHC), SEM imaging, mass spectrometry, ELISA, and quantitative DNA assays have confirmed the reduction of cells, cell fragments, cell‐associated proteins, and nucleic acids in chemically decellularized cartilage. [10a,c,d],, Chemical decellularization methods such as 2% SDS treatment for 2 h or tritonX‐100, EDTA and nuclease treatment have also shown that the DCC can retain collagen II and GAGs in the material and has been confirmed by immunofluorescent staining, histological staining, 1‐9‐dimethylmethylene blue (DMMB) sulfated GAG assay, and chloramine‐T hydroxyproline assay . The amount of GAG retained in DCC, however, significantly decreased with increasing chemical decellularization, while collagen II levels did not significantly decrease .…”
Section: Native Cartilage Matrixmentioning
confidence: 99%
“… Various formulations of DNases and RNases are also commonly used to remove nucleic acids from the material. [10d], Many chemical decellularization protocols encompass some combination of these chemicals. Because of the dense nature of articular cartilage, to improve the efficiency of chemical decellularization the native macrostructure must often be disrupted, which allows the material to be more effectively exposed to the chemical decellularization agents for shorter amounts of time .…”
Section: Native Cartilage Matrixmentioning
confidence: 99%
“…SAM2 gene was expressed and cystathione-β-synthase gene was knocked out from P. pastoris for production of SAM (He et al 2006; Yu and Shen 2012). Enhanced accumulation of SAM was achieved by manipulating the culture conditions like increased oxygen levels and nitrogen source (Chen et al 2007; Zhang et al 2008a; Zhang et al 2008b; Chu et al 2013). Earlier studies reported elevated intracellular production of SAM using recombinant P. pastoris; however, these reports did not confirm the expression of the enzyme by SDS-PAGE analyses, and molecular characterization of the accumulated SAM using MS/MS method.…”
Section: Introductionmentioning
confidence: 99%